The Influence of Quality of Work Life on Organizational Commitment: The Mediating Role of Job Satisfaction - Pant, Dinesh Kumar (Journal of Nepalese Management and Research, 2025)
The research aims to examine the influence of Quality of Work Life (QWL) on Organizational Commitment (OC), with the mediating role of Job Satisfaction (JS), and provides insights into organizational success. A quantitative approach was employed, collecting data from 405 employees through structured questionnaires using Likert scales. Descriptive statistics, correlation analysis, and regression-based mediation analysis (using Smart PLS) were applied to test the hypotheses. This study indicates that QWL significantly positively affects both JS and OC. JS partially mediates the QWL-OC relationship, explaining the variance in OC. The findings suggest that improving QWL enhances JS, thereby strengthening OC. The study is limited by a cross-sectional design, potential response bias, and a focus only on the communication sector, limiting generalizability and therefore leaving room for future research. This study contributes originality by exploring the QWL-OC-JS relationship in Nepal’s under-researched Karnali Province, offering sector-specific insights for policymakers and organizations to foster employee well-being and commitment.